Analysis Basic Laboratory Skills of Preservice of Chemistry Teachers - kamaludin, agus; Riksa Yustiana, Yusi (JURNAL PENDIDIKAN SAINS (JPS), 2024)
This research aims to determine the basic laboratory skills of prospective chemistry teacher students and the number of chemistry practicums in higher education that support chemistry practicum in high school. This research is quantitative and descriptive. The subjects in this research were lecturers who taught basic chemistry practicum and chemistry education students as preservice chemistry teachers. The data collection techniques used were document studies, interviews, and questionnaires. The research instruments used were interview guidelines and questionnaire sheets. The research results show that the knowledge of basic laboratory technical skills of chemistry education students at UIN Sunan Kalijaga is still a good criterion. Skills that need improvement include calibrating digital and mechanical balances and making synthetic indicator solutions. As many as 33.3% of university practicum titles support school chemistry practicums. Therefore, follow-up action is needed to prepare chemistry teachers who master the concepts and skills of good basic laboratory techniques as provisions for guiding chemistry practicums in high school.